2021
DOI: 10.1175/jpo-d-20-0080.1
|View full text |Cite
|
Sign up to set email alerts
|

The shelf sources of estuarine inflow

Abstract: The inflow to an estuary originates on the shelf. It flushes the estuary and can bring in nutrients, heat, salt, and hypoxic water, having consequences for estuarine ecosystems and fjordic glacial melt. However, the source of estuarine inflow has only been explored in simple models that do not resolve interactions between inflow and outflow outside of the estuarine channel. This study addressed the estuary inflow problem using variations on a three-dimensional primitive equation model of an idealized estuarine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…Even during a period of downwelling favorable winds, the freshwater transport in the coastal current is less than 1/2 of the estuarine freshwater outflow. Brasseale and MacCready (2021) found that the gentle slope promoted the downstream transport, while the upstream transport on the steep slope disappeared, which is consistent with our results. Therefore, we can conclude that bottom attachment promotes alongshore transport.…”
Section: B a Figure 12supporting
confidence: 93%
See 3 more Smart Citations
“…Even during a period of downwelling favorable winds, the freshwater transport in the coastal current is less than 1/2 of the estuarine freshwater outflow. Brasseale and MacCready (2021) found that the gentle slope promoted the downstream transport, while the upstream transport on the steep slope disappeared, which is consistent with our results. Therefore, we can conclude that bottom attachment promotes alongshore transport.…”
Section: B a Figure 12supporting
confidence: 93%
“…On the one hand, the sloping bottom in laboratory experiments cannot be made at a similar slope as the actual continental shelf. It is impossible to make the slope as gentle as 0.01 (or even 0.001) in the numerical models (Yankovsky and Chapman, 1997;Brasseale and MacCready, 2021), so the bottom-attached plume we observed still has a noticeable bulge. Although we cannot simulate the phenomenon in reality, our conclusion is still applicable when the slope is very gentle.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…𝐴𝐴 𝐴𝐴𝑜𝑜 is a reference density; 𝐴𝐴 𝐴𝐴 𝑆𝑆𝑆𝑆 , 𝑣𝑣 𝑆𝑆𝑆𝑆 and 𝐴𝐴 𝐴𝐴 𝑆𝑆𝑆𝑆 are the x, y and z Stokes drift velocities; 𝐴𝐴 𝐴𝐴 𝐵𝐵 𝑥𝑥 and 𝐴𝐴 𝐴𝐴 𝐵𝐵 𝑦𝑦 are the non-wave body forces; 𝐴𝐴 𝐴𝐴 WEC 𝑥𝑥 and 𝐴𝐴 𝐴𝐴 WEC 𝑦𝑦 are the non-conservative wave terms; and 𝐴𝐴 𝐴𝐴 is the eddy viscosity(Brasseale & MacCready, 2021;Kumar et al, 2012).…”
mentioning
confidence: 99%